Peran manajemen SDM dalam pengembangan karir karyawan pada PT. Atlas Resources Tbk Jakarta Selatan - Dede Andi; Melda Wiguna (e-Jurnal Ekonomi Sumberdaya dan Lingkungan, 2022)
The purpose of this study is to examine and explain how the role of human resource management in the career development of employees at PT. Atlas Resources Tbk South Jakarta. The research method used is to use a qualitative design with data collection techniques in the form of observation, interviews and documentation. This research is a field research where the problem posed in this study is determined by the current problem, so for this research is a qualitative research with a phenomenological approach. This study uses a phenomenological approach where the author will see a reality related to the role of human resource management in the career development of employees at PT Atlas Resources Tbk, South Jakarta. To determine the role of human resource management in employee career development indicators are used, the indicators used include fair treatment in a career, concern for direct superiors, information about various promotion opportunities, interest in being promoted, and level of satisfaction. Role can be defined as a distinctive behavior that characterizes each person in a work group or social context that has a large influence on an event, while career development is a formal effort to improve and add abilities that are expected to have an impact on the development and expansion of knowledge, thereby opening up the opportunity to get a position or title that satisfies the life of an employee. From the research results it is known that the role of human resource management in employee career development at PT. Atlas Resources Tbk is in accordance with their respective functions, that each line, each department has its own role and function in accordance with the existing organizational structure in the company. Therefore, employees must be managed properly, namely by helping employees plan their future careers in the company so that employees and the company can develop themselves to the maximum so that they can assist the organization in achieving predetermined organizational goals.